(untitled) (Medical Forum Monthly, 2024)
Objective: To analyze the pattern of hand injuries in terms of age, occupation, mechanism, type of injury and structures involved in patients with hand injuries visiting Liaquat National Hospital, Karachi. Study Design: Descriptive case series. Place and Duration of Study: This study was conducted at the Accidents and Emergency Department, Liaquat National Hospital, Karachi from Jan 2015 to June 2015. Materials and Methods: The records of 2367 patients reported for hand injuries were analyzed. Collected data were categorized on the basis of normal handedness, Gender, age, place of injury, mechanism of trauma, types of injuries and its association with different mechanisms. The results were statistically analyzed using mean, frequency and ranges. Results: Hand injuries constitute total 6% of hospital emergency visits with 75% (n=1775) male patients. Right hand dominance (91%) was seen but there was no significant difference in the involvement of right and left hand in injury. Young population (Age 16-35) was found most frequently suffered from hand trauma. Laborer and mechanical workers are the most affected personnel (30.7%) followed by office workers and students 27.3% and 23.9%, respectively. RTA and home were among the most common places of injury. Sharp cut and RTA were the main mechanisms of injury followed by machine/ crush injuries with fracture as the most common type of injury. Conclusion: Young male population is at significant risk of hand trauma. Road traffic accident, industry and home are most common places. Proper understanding of mechanism of injuries and timely referral to hand specialist are key steps in appropriate management.